Odczucia triathlonistów przed rywalizacją sportową = The triathletes feeling before sports competitions - Kostyra, Agnieszka (Journal of Education, Health and Sport, 2016)
Streszczenie Triathlon to połączenie trzech dyscyplin sportowych takich jak pływanie, kolarstwo, bieganie. Jak wiadomo na sukcesy sportowe składa się nie tylko sprawność fizyczna, ale także psychiczna. Badanie przeprowadzone na triathlonistach, zarówno mężczyznach i kobietach, miało na celu pokazanie jakie odczucia im towarzyszą, a także w jaki sposób radzą sobie oni ze stresem i innymi negatywnymi emocjami przed zawodami sportowymi. Przedstawiono także zaobserwowane różnice odczuć między mężczyznami i kobietami. Słowa kluczowe: triathlon, stres, trening psychologiczny, negatywne emocje Abstract Triathlon is a combination of three sport disciplines - swimming, cycling and running. As it is known sport achievements are made not only by physical efficiency but also by sportsmen’s psyche. A survey carried out on a group of triathletes, both men and women, was intended to show what are their feelings and how this group deals with stress and other negative emotion they feel before sport competition. There were also shown the observed differences between men’s and women’s feelings. Keywords: triathlon, stress, psychological training, negative emotions